1974
DOI: 10.3171/jns.1974.41.5.0590
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic pressure-flow relationships of brain blood flow in the monkey

Abstract: ✓ Pressure-flow data are presented for the brain vascular bed in the rhesus monkey. These data are obtained at fixed levels of vasomotor tone. Resultant flow curves are called the “dynamic pressure-flow relationships” (DPFR). In the experimental model, arterial pressures are oscillated with a sinusoidal pump at frequencies exceeding the vasomotor response lag time. The resultant DPFR curves are discussed. A model is presented to show that changes in vasomotor tone cause a vertical shift of the DPFR. Changes in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
19
0
2

Year Published

1982
1982
2022
2022

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(21 citation statements)
references
References 10 publications
0
19
0
2
Order By: Relevance
“…However, when dynamic measurement techniques are used, such as electromagnetic flowmetry or ultrasound Doppler, the limitations of this concept become manifest. 1,2 Dynamically, flow may stop at pressure levels significantly higher than zero. The arterial blood pressure (ABP) level at which flow stops is defined as the critical closing pressure (CCP) [1][2][3] or, in cardiac literature, the zero-flow pressure (P fϭ0 ).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…However, when dynamic measurement techniques are used, such as electromagnetic flowmetry or ultrasound Doppler, the limitations of this concept become manifest. 1,2 Dynamically, flow may stop at pressure levels significantly higher than zero. The arterial blood pressure (ABP) level at which flow stops is defined as the critical closing pressure (CCP) [1][2][3] or, in cardiac literature, the zero-flow pressure (P fϭ0 ).…”
mentioning
confidence: 99%
“…1,2 Dynamically, flow may stop at pressure levels significantly higher than zero. The arterial blood pressure (ABP) level at which flow stops is defined as the critical closing pressure (CCP) [1][2][3] or, in cardiac literature, the zero-flow pressure (P fϭ0 ). 4 Above the CCP, an approximately linear slope, sometimes referred to as the inverse flow resistance, defines the relation between pressure and flow, when these variables are plotted as an x-y function 1,2 ( Figure 1).…”
mentioning
confidence: 99%
“…[2][3][4][5][6][7] When large pneumatic cuffs placed around both thighs are inflated above systolic pressure for Ն2 minutes and then suddenly released, a sharp drop in ABP is usually observed, lasting Ϸ10 seconds before returning to its original level. A simultaneous drop in cerebral blood flow velocity (CBFV), usually estimated with Doppler ultrasound, 8 accompanies the fall in ABP.…”
mentioning
confidence: 99%
“…The inflow pressure at which flow reaches zero is called the critical closing pressure (CrCP) [3, 4]. Dewey et al [5 ]and Early et al [6 ]demonstrated in monkeys that CrCP is the primary variable affecting cerebral blood flow. They also identified vasomotor tone and ICP as the main determinants of CrCP.…”
Section: Introductionmentioning
confidence: 99%